Potential effects of sweet potato (ipomoea batatas) in hyperglycemia and dyslipidemia—a systematic review in diabetic retinopathy context - Ruth Naomi; Hasnah Bahari; Muhammad Dain Yazid; Fezah Othman; Zainul Amiruddin Zakaria; Mohd Khairi Hussain (MDPI AG, Basel, Switzerland, 2021)
Hyperglycemia is a condition with high glucose levels that may result in dyslipidemia. In severe cases, this alteration may lead to diabetic retinopathy. Numerous drugs have been approved by officials to treat these conditions, but usage of any synthetic drugs in the long term will result in unavoidable side effects such as kidney failure. Therefore, more emphasis is being placed on natural ingredients due to their bioavailability and absence of side effects. In regards to this claim, promising results have been witnessed in the usage of Ipomoea batatas (I. batatas) in treating the hyperglycemic and dyslipidemic condition. Thus, the aim of this paper is to conduct an overview of the reported effects of I. batatas focusing on in vitro and in vivo trials in reducing high glucose levels and regulating the dyslipidemic condition. A comprehensive literature search was performed using Scopus, Web of Science, Springer Nature, and PubMed databases to identify the potential articles on particular topics. The search query was accomplished based on the Boolean operators involving keywords such as (1) Beneficial effect OR healing OR intervention AND (2) sweet potato OR Ipomoea batatas OR traditional herb AND (3) blood glucose OR LDL OR lipid OR cholesterol OR dyslipidemia. Only articles published from 2011 onwards were selected for further analysis. This review includes the (1) method of intervention and the outcome (2) signaling mechanism involved (3) underlying mechanism of action, and the possible side effects observed based on the phytoconstiuents isolated. The comprehensive literature search retrieved a total of 2491 articles using the appropriate keywords. However, on the basis of the inclusion and exclusion criteria, only 23 articles were chosen for further review. The results from these articles indicate that I. batatas has proven to be effective in treating the hyperglycemic condition and is able to regulate dyslipidemia. Therefore, this systematic review summarizes the signaling mechanism, mechanism of action, and phytoconstituents responsible for those activities of I. batatas in treating hyperglycemic based on the in vitro and in vivo study.